Peningkatan Kinerja Guru dalam Pengembangan Evaluasi Hasil Belajar Melalui Supervisi Akademis Kepala Sekolah - Ahmad Mujitahid (Journal of Classroom Action Research, 2022)
The purpose of this research is to improve teacher performance in the development of evaluation of learning outcomes through the academic supervision of the principal in SD Negeri 46 Ampenan Year of Study 2019/2020. Research in this school is carried out in 3 cycles with each implementation consisting of planning, action, observation, and reflection. In data analysis the techniques used are quantitative. The results showed that: (1) Principal Coaching in an effort to improve teacher performance through academic supervision of the Principal showed improvement in each round (Cycle); (2) Activities in coaching activities show that all teachers can improve their performance well in every aspect; (3) Improvement of teacher performance by the Principal through academic supervision of the Principal shows an improvement in each round; (4) The principal's activities show that coaching activities through academic supervision of the Principal are useful and can help teachers to more easily understand the concept of teacher roles and functions so that teacher performance can improve.